The Advisory Opinion of the International Court of Justice on Chagos: a critical overview (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2022)
ABSTRACT:This case discussion seeks to draw attention to the Advisory Opinion by the International Court of Justice on 25 February 2019 concening the Chagos Arpichelago (Advisory Opinion on the Legal Consequences of the Separation of the Chagos Archipelago from Mauritius in 1965). It underlines the legal arguments on the issue of the right to self-determination and the decolonisation process. The ICJ has highlighted the importance of the right to self-determination in the post-colonial context and upheld the necessity for the decolonisation process of Mauritius to be completed. The strong legal stand by the ICJ taken against the UK, despite the latter being a powerful state, is noteworthy. This Advisory Opinion is decisive not only for the Chagossians and their fate, but also for other African jurisdictions grappling with the issue of self-determination and an incomplete decolonisation process. The Opinion re-calibrates the debate on these two important international law issues by serving as an essential judicial tool to be applied in other similar cases. TITRE ET RÉSUMÉ EN FRANCAIS:L’avis consultatif de la Cour internationale de Justice sur l’Archipel des Chagos: aperçu critiqueRÉSUMÉ:Le présent commentaire d’arrêt vise à disséminer l’avis consultatif de la Cour internationale de justice (CIJ) sur l’Archipel des Chagos et met l’accent sur les arguments juridiques essentiels y énoncés au sujet du droit à l’autodétermination et du processus de décolonisation. La CIJ a souligné l’importance du droit à l’autodétermination dans le contexte postcolonial et a confirmé la nécessité de parachever le processus de décolonisation de l’Ile Maurice. Il convient de souligner la position juridique forte adoptée par la CIJ contre le Royaume-Uni, bien que ce dernier soit un État puissant. Cet avis consultatif est décisif non seulement pour les Chagossiens et leur destin, mais également pour les autres collectivités africaines en quête d'autodétermination et du parachèvement de leur processus de décolonisation. L'avis réajuste le débat sur ces deux importantes questions de droit international en servant d'instrument judiciaire important à appliquer dans des affaires similaires.
Keywords: International Court of Justice; Chagos; Mauritius; United Kingdom; self-determination